Friday, 15 June 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.2063
|View full text |Cite
|
Sign up to set email alerts
|

FRI0693 Fears and misconceptions of women with chronic rheumatic diseases on their journey to motherhood

Abstract: Background:Recent EULAR ‘Points to Consider’ provide guidance on management and treatment of Women of Childbearing Age (WoCBA) with chronic rheumatic diseases (CRD: RA, axSpA, PsA). However, it is still unclear if these patients (pts) feel adequately supported to make informed treatment decisions around pregnancy and breastfeeding.Objectives:To gain insight into perspectives of women with CRD regarding disease management and pregnancy, and assess whether current clinical practice provides adequate support.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
2
10
0
1
Order By: Relevance
“…The small proportion of women receiving methotrexate during pregnancy (0.7%) could be attributed to these prescriptions being issued before the pregnancy became known. This is supported by a previous study that suggested that half of pregnancies in women of childbearing age with chronic rheumatic disease are not actively planned [ 32 ]. Furthermore, the TNFi treatments adalimumab and etanercept have been recommended for use during the first part of pregnancy (until gestation week 20 and 30–32, respectively) and breastfeeding, and the TNFi treatment certolizumab pegol has been recommended for use throughout pregnancy and breastfeeding [ 19 ].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The small proportion of women receiving methotrexate during pregnancy (0.7%) could be attributed to these prescriptions being issued before the pregnancy became known. This is supported by a previous study that suggested that half of pregnancies in women of childbearing age with chronic rheumatic disease are not actively planned [ 32 ]. Furthermore, the TNFi treatments adalimumab and etanercept have been recommended for use during the first part of pregnancy (until gestation week 20 and 30–32, respectively) and breastfeeding, and the TNFi treatment certolizumab pegol has been recommended for use throughout pregnancy and breastfeeding [ 19 ].…”
Section: Discussionsupporting
confidence: 73%
“…The overall reduction in treatment for women with IRD during pregnancy observed in this study, including the reduction in new prescriptions by GPs and gynecologists and the low level of prescriptions by internal medicine and rheumatology specialists, is likely linked to concerns over the impact of treatment on pregnancy outcomes. This is supported by a recent survey in women of childbearing age with axSpA, PsA, and RA, which reported that stopping treatment during pregnancy was driven by the fear of harming the fetus in 78% of women [32]. The observed lack of return to treatment after delivery in this study could be linked to concerns over the impact of treatment on breastfeeding.…”
Section: Fig 4 Continuedsupporting
confidence: 77%
See 2 more Smart Citations
“…Аналогичные проблемы имеют место и в других странах. По данным многоцентрового исследования [5], проведенного в ряде стран Западной Европы, США и Японии и включавшего опрос более 1000 пациенток с ревматическими заболеваниями (РЗ), в т. ч. большой группы больных спондилоартритами (СпА), 47% женщин при наступлении беременности прекратили лечение иФНО-α по совету врача и ещё 22% самостоятельно приняли решение о прекращении этой терапии. По данным T. Haroun и соавт.…”
Section: Discussionunclassified